IMPLEMENTASI MANAJEMEN BANDWIDTH BERBASIS MIKROTIK MENGGUNAKAN METODE PCQ (PER CONNECTION QUEUE) PADA SMK YAJ DEPOK - Ari Saputra; Jordy Lasmna Putra (Jurnal Informatika dan Teknik Elektro Terapan, 2023)
Abstract. Over time, the development of Information Technology is increasing rapidly, in which almost every company has a computer network that supports the flow of information within the company. YAJ Depok Vocational School is an example of an internet user engaged in education. The slow internet network is often complained of by SMK YAJ Depok school employees because one or more clients/users use the network because the activities of each user are downloading and uploading simultaneously which will result in uneven bandwidth on the network. With this problem, a solution was made for the problem that was at SMK YAJ Depok, it was necessary to implement bandwidth management with the MikrotikOS router to distribute bandwidth evenly to active clients/users using the PCQ (PER Connection Queue) method. Aims to provide and maximize the optimal use of bandwidth to each client. With the implementation of the implementation of bandwidth management using the PCQ (PER Qonection Queue) method, it can produce fair and equitable bandwidth usage for each client